Proactivity in the workplace: the role of flow in the relationship between proactivity and subjective well-being - Sleiman Haidar, Sarah N. (Kansas State University, 2019)
In the constantly changing world of work, employees are expected to be proactive by taking initiative and being self-starting, future focused, and change oriented. Consequently, research around proactivity has grown exponentially over the last two decades. However, the relationship with employee well-being has been widely neglected. This research addressed this gap by investigating the dynamics between employee proactivity and subjective well-being, while taking work-related flow into account. With the use of a diary method, this study provided support that proactivity is not necessarily a burden on psychological well-being. Instead, proactivity in its dispositional and behavioral form of task crafting, was found to have a direct impact on optimal work experiences and well-being outcomes such as subjective vitality and positive affect. Acknowledging the complexity of the relationships, this study also tested mediated and moderated paths and provided several theoretical and practical contributions.
Keywords: Psychological well-being; Proactivity at work; Task crafting; Flow at work; Proactive personality; Work and employee well-being